Opportunities to Learn in America’s Elementary Classrooms - Pianta, Robert C. (2007)
Observations in 737 5(th)-grade classrooms reveal high amounts of basic skills instruction in reading and math as whole-group or individual-seatwork, delivered with mediocre instructional quality. Cooperative learning, technology, social studies or science are rare. Observed opportunities show little association with features of teachers or schools. Across 1(st), 3(rd) and 5(th) grades, classroom quality is low if children are poor or are low on achievement; for others quality is inconsistent across grades. The promise of legislative mandates for high quality educational programs will depend on more accurate assessments of teaching and must address inequity in access to high-quality educational experiences.